Draft Annual Plan 2004-2005 Government of Mizoram - Planning Commission (Planning Commission, 2004)
Mizoram is situated in the southern-most comer of the North Eastern Region and is bounded on the north by the States of Assam and Manipur, on the east and south by Chin Hills of Myanmar and on the west by Chittagong Hill Tracts of Bangladesh and the State of Tripura. It covers an area of 21,087 Sq.Km. It has an International Boundary of 404Kms. with Myanmar and 318Kms with Bangladesh. The population of Mizoram as per 2001 Census is 8,91,058 with a density of 33 per Sq.Km. Literacy as per 2001 census is 82.27% which is the second highest in the country. Mizoram has one Air-Link i.e. Lengpui Airport which is about 42kms away from Aizawl and there is rail head upto Bairabi. The National Highway No.54 connects Mizoram from Cachar District of Assam.
Planning & Programme Implementation Department, Government of Mizoram